Improved charge transportation at PbS QDs/TiO2 interface for efficient PEC hydrogen generation. Issue 23 (27th May 2016) - Ikram, Ashi; Sahai, Sonal; Rai, Snigdha; Dass, Sahab; Shrivastav, Rohit; Satsangi, Vibha R.
Abstract : Inclusion of PbS QDs underneath TiO2 thin film has been proven to be an effective strategy in enhancing the PEC response of TiO2 owing to higher number of photogenerated charge carriers & their efficient separation, along with long term stability. Abstract : The effect of lead sulfide (PbS) quantum dots (QDs) on the photoelectrochemical properties of TiO2 with a varied number of SILAR cycles has been investigated. The study has also highlighted physical processes including band alignment, charge recombination and transportation for a PbS QDs/TiO2 interface. The inclusion of PbS QDs underneath TiO2 thin film has significantly enhanced the PEC response due to a higher number of photogenerated charge carriers along with the efficient separation and facilitation of these carriers towards their respective electrodes. The uniqueness of the work lies in the high stability of the system as PbS QDs lie beneath the TiO2 thin film, compared to the commonly used QDs sensitization over metal oxide, along with a good photoresponse.